Clinical outcomes of percutaneous screw fixation of acetabular fracture: A minimally invasive procedure - Khalid A. Alsheikh, MD; Abdullah M. Alzahrani, MD; Ali S. Alshehri, MD; Faisal A. Alzahrani, MD; Yousef S. Alqahtani, MD; Mohammed I. Alhumaidan, M.B.B.S; Hussam S. Alangari, M.B.B.S (Journal of Taibah University Medical Sciences, 2023)
الملخص: أهداف البحث: يعد اجراء الاختزال المفتوح مع التثبيت الداخلي بمثابة العلاج القياسي للكسور الحقية. تثبيت الكسور الحقية بالمسمار عن طريق الجلد هو اجراء جديد مرغوب فيه بسبب التشريح المعقد للحوض. في هذه الدراسة، هدفنا تقييم النتائج الوظيفية والحركية ومعدل الشفاء والتشوهات الوعائية العصبية البعيدة في المرضى الذين خضعوا لتثبيت الكسور باستخدام المسمار بالطريق الراجع عن طريق الجلد طرق البحث: شملت دراستنا ۳٦ مريضا يعانون من الكسور الحقية ممن خضعوا للعلاج بطريقة تثبيت الكسور بالمسمار عن طريق الجلد وذلك خلال الفترة من يناير ٢٠۱٦ الى يونيو٢٠٢۱, منهم ۱٨ حالة مصابة بالكسور الحقية في منطقة العمود الأمامي و٧ مصابين بالكسور الحقية على المستوى المستعرض و ۱۱ مصابين بالكسور الحقية المصاحبة منهم ٦ مصابين بكسور حقية على شكل حرف ت. تم وصف الخصائص والنتائج السريرية بالتكرار والنسب المئوية للمتغيرات الفئوية، والمتغيرات المستمرة كقيمة متوسط وانحراف معياري، وتم استخدام برنامج الحزمة الإحصائية للعلوم الاجتماعية للتحليل الإحصائي النتائج: بلغ متوسط الوقت لاستعادة القدرة على الحركة الكاملة مع تحمل الوزن الكامل ۱٢٫٩±٫٤ ٥ أسبوعا، بالإضافة الى حوالي ۱۱٫۱±٫٨ ٢ لاختفاء الألم مع التئام الكسور بشكل مرض. ظهرت اقلية من المرضى بلغت ٨٫۳٪ تعاني من تشوهات تؤثر على الجهاز الوعائي العصبي القاصي بالإضافة الى۱۱٫۱ ٪ من المرضى الذين عانوا من اختلال وظيفي جنسي. تم تقييم شدة الألم أيضا باستخدام مقياس تناظري بصري، وكان متوسط شدة الألم في اليومين الأول والثالث بعد الجراحة ٤±٫٤ ٢و ۳٫٨ ±٫٦ ٢ على التوالي بينما بلغ متوسط شدة الألم قبل الخروج من المستشفى ۱٫٧ ±٢٫٦ الاستنتاجات: يعد التثبيت بالمسمار عن طريق الجلد بديلا جراحيا آمنا وفعالا لمعظم الكسور الحقية Abstract: Objective: Open reduction with internal fixation is the surgical intervention of choice for acetabular fractures (AFs). Percutaneous screw fixation for AFs is a new procedure that is desirable because of the complex anatomy of the pelvis. In this study, we aimed to assess the functional outcomes, mobility, healing, and distal neurovascular abnormalities in patients who underwent percutaneous retrograde screw fixation. Methods: Our study included 36 patients with AFs treated with percutaneous screw fixation between January 2016 and June 2021. There were 18 cases with anterior column AF, 7 cases with transverse AF, and 11 cases with associated AF, 6 of which had a T-shaped AF. Frequencies and percentages were used to describe characteristics and clinical outcomes. Mean and standard deviation were used for continuous variables. SPSS version 23 (IBM Corporation, Armonk, NY, USA) was used for statistical analysis. Results: The average time to regain full mobility with full weight bearing was 12.9 ± 5.4 weeks, and approximately 11.1 ± 2.8 weeks was required for patients to be pain-free with satisfactory fracture healing. Only a minority (8.3%) of patients had abnormalities affecting the distal neurovascular system, and 11.1% experienced sexual dysfunction. Pain severity was assessed with a visual analogue scale. The average pain severity on the first and third post-operative days was 4 ± 2.4 and 3.8 ± 2.6, respectively. However, the average pain intensity before discharge was 1.7 ± 2.6. Conclusion: Percutaneous screw fixation is the most efficient surgical choice for most pelvic/AFs.